GROUND AND DARKLING BEETLES (COLEOPTERA: CARABIDAE, TENEBRIONIDAE) FROM KARGIL, J AND K - MOHD FEROZ,; J. S. TARA, (The Bioscan, 2010)
Kargil district of J and K state was surveyed during the year 2007-2008 to record the insect fauna belonging to family Carabidae and Tenebrionidae (Coleoptera). A total of seven identified genera viz., Lebia sp., Amara, sp., Bembidion spp., Calosoma sp. (Carabidae) and Gonocephalum sp., Blaps sp. and Cyphogenia sp. (Tenebrionidae) within these two families belonging to two suborders, two superfamilies and five sub families were recorded. Besides their records their distribution in the area and diagnostic features are also incorporated in this communication.